DEVELOPMENT OF A FOOTBALL PASSING LEARNING MODEL FOR JUNIOR HIGH SCHOOL STUDENTS - Alparis, Lutvi (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Abstract The aim of this research is to produce a product in the form of Developing a Football Passing Learning Model for Class Middle School Students. Analyze the process of developing a soccer passing learning model for class students, analyze the feasibility of the learning model, and assess its effectiveness. It is hoped that this research will produce a model that is not only suitable for use, but also effective in improving soccer Passing skills in class junior high school students. In its development, it uses the ADDIE method, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The research sampling technique used in this study was 108 students. Data analysis uses effectiveness test analysis of the Football Passing model that was developed. Based on test data analysis, it is known that the pretest average is 24.2221 and the posttest is 39.7352. Then the researcher carried out a paired sample test to determine the level of significance of the model given to the subject. Stating that the significance level is 0.000 < 0.05, it can be concluded that the development of a soccer passing learning model can significantly improve student learning outcomes to be applied in the soccer passing learning process. The results of the pretest and posttest also showed significant results.